Communication Scheme of Modbus-Profibus Motor Protection Controller Based on STM32 - Run, Ze (International Journal of Computer Science and Information Technology, 2024)
Motor protection as one of the protection measures of power electronic system, has always been conservative attention, the content of this paper is based on the communication process of low-voltage motor protection. This paper discusses from the perspective of cost reduction and efficiency enhancement and industrial capability enhancement. Therefore, VPC3 chip of Siemens is not used as the protocol package of Profibus communication, and its packet and decoding are both using MCU internal resources. Modbus, as a simple and easy to understand communication mode, is used as the underlying data exchange library of Profibus. Profibus communication protocol only needs to encapsulate Modbus for motor protection, and realizes two communication protocols for motor protection controller. In this connection, a communication scheme based on STM32 Modbus-PROFIBUS motor protection controller is proposed.